Molecular-barrier-enhanced aromatic fluorophores in cocrystals with unity quantum efficiency - Ye, Huanqing (2020)
Singlet–triplet conversion in organic light‐emitting materials introduces non‐emissive (dark) and long‐lived triplet states, which represents a significant challenge in constraining the optical properties. There have been considerable attempts at separating singlets and triplets in long‐chain polymers, scavenging triplets, and quenching triplets with heavy metals; nonetheless, such triplet‐induced loss cannot be fully eliminated. Herein, a new strategy of crafting a periodic molecular barrier into the π‐conjugated matrices of organic aromatic fluorophores is reported. The molecular barriers effectively block the singlet‐to‐triplet pathway, resulting in near‐unity photoluminescence quantum efficiency (PLQE) of the organic fluorophores. The transient optical spectroscopy measurements confirm the absence of the triplet absorption. These studies provide a general approach to preventing the formation of dark triplet states in organic semiconductors and bring new opportunities for the development of advanced organic optics and photonics.